Effects of Cognitive Pain-coping Strategies and Locus of Control on Perception of Cold Pressor Pain in Healthy Individuals: Experimental Study - Jokić-Begić, Nataša (Array, 2009)
Background The aim of the present study was to determine the effectiveness of the coping strategies – distraction and redefining – on pain experience in individuals with internal vs external locus of control. Method The participants were exposed to pain induced by cold pressor procedure. Pain tolerance, pain intensity, and objective and subjective duration of pain were measured in three different situations. In the control situation, the participants did not use any cognitive pain coping strategy. In two other situations, they used distraction and redefining strategies, respectively. Results Internally- and externally-oriented participants did not differ in pain tolerance, pain intensity ratings, and subjective duration of painful stimulation in any of the three situations. The use of cognitive pain coping strategies increased pain tolerance in both groups in comparison with the control situation. In both situations, the participants underestimated the duration of pain tolerance. There was no difference between the effectiveness of distraction and redefining strategies on pain tolerance and pain intensity ratings. Conclusion Cognitive pain coping strategies increase the duration of pain tolerance irrespective of the individual’ s locus of control, but have no effect on pain intensity rating.